2006
DOI: 10.1007/s00134-005-0059-4
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent for research in ICU obtained before ICU admission

Abstract: in a study, and 9/36 (25%) could not recall the study purpose and the related risk. Patients with incomplete recall stayed longer in ICU [median (range): 4 (3-6) vs 3 (1-5) days; p = 0.004]. None of these patients (0/9 vs 10/27; p < 0.04) had read the informative leaflet AND asked at least one question during the informed consent procedure. Conclusions: Even when the informed consent is obtained in the most optimal conditions for ICU research, its ethical value remains questionable. Indeed, a substantial numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…Other studies, including those on patients with acute myocardial infarction, have reported clinical trial participation recall rates similar to ours [14-16]. Our rate is also similar to the rate we found in a study in which informed consent was obtained in an ideal situation, namely before ICU admission [9]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Other studies, including those on patients with acute myocardial infarction, have reported clinical trial participation recall rates similar to ours [14-16]. Our rate is also similar to the rate we found in a study in which informed consent was obtained in an ideal situation, namely before ICU admission [9]. …”
Section: Discussionsupporting
confidence: 88%
“…As objective criteria regarding the decision-making capacity of patients are lacking in international and national directives, investigators usually use their clinical judgement and the Glasgow Coma Scale (GCS) as guidance. Previously, we showed that 22% of clinical trial participants could not recall their participation in the clinical trial despite the fact that informed consent was obtained in an ideal situation, namely before their admission to the ICU [9]. Furthermore, 25% of patients were unable to recall the clinical trial purpose and its related risks.…”
Section: Introductionmentioning
confidence: 99%
“…Informed consent is considered essential to protect the patient and to respect the principle of autonomy. However, most ICU patients do not possess a capacity to understand, to make a judgement or to recall all the components of a proposed study 1 2. ICU patients therefore constitute a “vulnerable population” that requires special and reinforced protection 3.…”
mentioning
confidence: 99%
“…Furthermore, in an observational study among patients admitted to the ICU, judged to be competent (Glasgow coma scale score of 15, fully oriented and free of mechanical ventilation) and who accepted to participate in a research study, 80% of the patients recognized 10 to 12 days after informed consent had been obtained that they had accepted to participate in a clinical trial, but only 32% could recall the purpose of the trial and its related risks (18). The same authors also showed even lower recall rates in another study in the ICU setting (18). In these conditions, some ICU patients may be approached for consent to research on the understanding that they are competent, whereas in actual fact, they may have undetected delirium, cognitive impairment or poor recall, and consequently, reduced decision-making capacity.…”
Section: Decisional Incapacitymentioning
confidence: 99%